Dietary Supplementation of Spirulina platensis as a Substitute for Antibiotics in Arab Chicken (Gallus turcicus) - Hasna, N. A.; Widiastuti, E.; Agusetyaningsih, I.; Wulandari, E. C.; Murwani, R.; Yudiarti, T.; Sartono, T. A.; Sugiharto, S.; Wahyuni, H. I. (Tropical Animal Science Journal, 2024)
This study was conducted to determine the effect of adding Spirulina platensis to replace zinc bacitracin on performance, egg quality, blood profile, total gut bacteria, and liver histopathology of local indigenous Arab chicken (Gallus turcicus). One hundred and eight 28-week-old laying hens were distributed randomly to three treatments: T0 (control diet), T1 (T0 + 1% S. platensis), and T2 (T0 + 0.04% zinc bacitracin). The treatment was applied for 49 days. S. platensis and zinc bacitracin decreased feed intake (p